The Effectiveness of “Wizer.me” as Digital Learning Media to Improve Vocational Students’ Reading Comprehension of Narrative Text - Ramadhani Aktasan (Retain: Journal of Research in English Language Teaching, 2026)
This study investigated the effectiveness of Wizer.me as a digital learning medium in improving vocational high school students’ reading comprehension of narrative texts. The study employed a quantitative pre-experimental one-group pretest–posttest design involving 30 eleventh-grade students from the Visual Communication Design (DKV) program at a private vocational high school in Surabaya during the 2025/2026 academic year. A 30-item multiple-choice reading test was developed based on the TOEFL iBT Reading Framework, covering five reading skills: identifying main ideas, vocabulary in context, scanning for details, making inferences, and locating references. Students completed a pre-test, participated in three instructional sessions using interactive Wizer.me worksheets, and then completed a post-test. Data were analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, and a paired sample t-test. Results showed that the mean score increased from 70.13 (SD = 6.11) in the pre-test to 90.73 (SD = 6.87) in the post-test, indicating a gain of 20.60 points. The normality test indicated that the residuals were normally distributed (p = 0.079), and the paired sample t-test showed a statistically significant improvement (t = -14.663, df = 29, p < 0.001). These findings suggest that Wizer.me is an effective digital learning medium for enhancing vocational students’ reading comprehension of narrative texts